Kundzob: corpo-árvore - um processo de criação e meditação em ecoperformance - Lima, Elcivan Luciano de (2023)
This research proposes to discuss the process of creating ecopoetics in ecoperformance, which is based on the perspective of the Tibetan Buddhist's meditation as a process. With this, the objective is to provide the performer with an inner perception development during the creative process and the performative act. For this procedural trajectory, we resort to the elaboration of personal mythology, related to the circumstances of life and its relationship with the ecological behavior as a fundamental practice, intending to provide the performer, through his body, an encounter of full presence on alert for the performance art. Performative research was the approach used as a practical and creative investigation methodology to understand, in the everyday work, the propositions and relations established by the performative artist.